Dakar Framework for Action. Education for all: meeting our collective commitments - Autores, Varios (2000)
By meeting in Dakar, Senegal, in April 2000, we the participants in the World Education Forum pledge to achieve the goals and achievements of Education for All (EFA) for citizens and all societies